2005
DOI: 10.1111/j.1528-3577.2005.00214.x
|View full text |Cite
|
Sign up to set email alerts
|

Independence Day as a Cosmopolitan Moment: Teaching International Relations

Abstract: This essay expands upon a teaching approach that I used in my introductory international relations (IR) course for three semesters prior to September 11, 2001. The vast majority of the curriculum of the course is read through Independence Day, a 1996 blockbuster Hollywood film. Beginning with the film and the concept of world order it arguably provides through a fictional moment of world peace (or hegemony, depending how one interprets the leading role of the U.S. in the film and the significance of the Fourth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…One instructor found that “Film clips can create useful hooks for individual students to hang brand‐new theoretical questions upon (Waalkes ).” Some educational psychologists have found that students have a difficult time learning and recalling abstract concepts (Bruner and Anglin ; Kuzma and Haney ) and that film can be useful at dealing with this problem. In reference to teaching international relations theory, one teacher asserted, “students need to be able to view and identify with the various narratives used to describe international politics by first seeing them acted out and then only later can they understand them in conceptual form by referencing them as ‐isms (Webber :388).”…”
Section: Previous Research On Film In the International Studies Classmentioning
confidence: 99%
“…One instructor found that “Film clips can create useful hooks for individual students to hang brand‐new theoretical questions upon (Waalkes ).” Some educational psychologists have found that students have a difficult time learning and recalling abstract concepts (Bruner and Anglin ; Kuzma and Haney ) and that film can be useful at dealing with this problem. In reference to teaching international relations theory, one teacher asserted, “students need to be able to view and identify with the various narratives used to describe international politics by first seeing them acted out and then only later can they understand them in conceptual form by referencing them as ‐isms (Webber :388).”…”
Section: Previous Research On Film In the International Studies Classmentioning
confidence: 99%
“…Using movies or other forms of active-learning techniques, including simulations, role-plays, and games, is not new to political science as others acknowledge (Boyer 2002;Engert and Spencer 2009;Gregg 1998;Kuzma and Haney 2001;Lindley 2001;Simpson and Kaussler 2009;Sunderland, Rothermel, and Lusk 2009;Webber 2005;Weber 2001Weber , 2009. What is important here, however, is to establish the reason educators find it beneficial to rely on these types of teaching techniques.…”
Section: Movies To the Rescue 437mentioning
confidence: 94%
“…Efforts to explain and understand IR through LOTR take up the challenge posed by Christine Sylvester, a leading feminist critic of IR as a discipline, to turn to the humanities for greater understanding (Sylvester 2002b). Using mythology is one way of doing this and provides a very powerful tool for engaging in abstract concepts (see, e.g., Weber 2001, 2005; Weldes 2003; Webber 2005; Nexon and Neuman 2006). As Julie Webber (2005) argues, “The present generation, in general, lives in fantasy and in order to reach them one must go to their fantasy first, then begin to exile them from it” (389).…”
Section: Overview: the Lord Of The Rings And International Relationsmentioning
confidence: 99%